1997
DOI: 10.2307/3870442
|View full text |Cite
|
Sign up to set email alerts
|

Light-Dependent Spatial and Temporal Expression of Pigment Regulatory Genes in Developing Maize Seeds

Abstract: Both light and developmental stimuli are directly involved in the regulation of plant gene expression. In maize, activation of the anthocyanin pathway represents an excellent model system for studying the interactions between an external factor, such as light, and internal factors that regulate plant and seed development. By analyzing in detail the aleurone and pericarp seed layers, different developmental windows for light have been found in the two tissues[mdash]the former in the advanced stages of developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 27 publications
3
26
0
Order By: Relevance
“…There are many reports describing the effects of light on anthocyanin gene expression (Fuglevand et al, 1996;Kawabata et al, 1999;Koes et al, 1989;Procissi et al, 1997;Takos et al, 2006;Taylor and Briggs, 1990;Toguri et al, 1993). All these studies demonstrated that anthocyanin gene expression was light inducible.…”
Section: Daylengthmentioning
confidence: 99%
“…There are many reports describing the effects of light on anthocyanin gene expression (Fuglevand et al, 1996;Kawabata et al, 1999;Koes et al, 1989;Procissi et al, 1997;Takos et al, 2006;Taylor and Briggs, 1990;Toguri et al, 1993). All these studies demonstrated that anthocyanin gene expression was light inducible.…”
Section: Daylengthmentioning
confidence: 99%
“…These regulatory proteins belong to the MYB, bHLH and bZIP families, and the genes encoding these transcription factors may themselves be subjected to spatial, temporal and environmental regulation ( Dröge‐Laser et al . 1997 ; Procissi et al . 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…, Vitis vinifera L., V. vinifera x V. labrusca L. (Boss et al, 1996;Gollop et al, 2001;Kobayashi et al, 2001Kobayashi et al, , 2002Sparvoli et al, 1994), and Prunus persica (L.) Batch (Tsuda et al, 2004). Studies led to the conclusion that the pigment is synthesized when at least two kinds of genes are expressed: structural genes, encoding the enzymes catalyzing the reactions of the metabolic pathway, and regulatory genes, encoding the transcription factors controlling their expression (Dooner et al, 1991;Goodrich et al, 1992;Procissi et al, 1997;Quattrocchio et al, 1993). Therefore, any signifi cant genetic occurrence, in even one of the structural or regulatory genes, may result in the loss of production of the pig-ment.…”
mentioning
confidence: 99%